Diversity of Fodder Plants of Betalghat Block, Nainital district, Western Himalaya - Pandey, Naveen Ch.; Joshi, G.C.; Tewari, Lalit M.; Pangtey, Y.P.S. (International Journal of Environment, 2018)
The Himalaya is well recognized for its bio-physical diversity and socio-cultural heritage, traditional systems and an ample quantity of indigenous knowledge. The study was conducted with the help of Participatory Rural Appraisal (PRA) tool to document the diversity of fodder plants of Betalghat Block of Nainital District (Western Himalaya). Total 210 fodder plants species belonging to 70 families, 164 genera of different habits such as trees (35%), shrubs (31%), herbs (25%), and climbers (9%), were recorded. Out of 70 families, 12 dominant families were Poaceae (18 species), followed by Fabaceae (16 species), Moraceae (10 species), Rosaceae (10 species), Asteraceae (8 species), Euphorbiaceae (7 species), Mimosaceae (6 species), Caesalpinaceae (5 species), Ranunculaceae (5 species), Rhamnaceae (5 species), Urticaceae (5 species) and Rubiaceae (5 species). Of the total recorded species, 41% of the species were used during winter days, 38% during summer and 21% throughout the year. For each species, scientific and vernacular names, multipurpose uses (Fuel, medicinal, timber, agricultural tools, religious and fiber) were used. For the conservation of fodder plant species prioritization, mass multiplication with afforestation, reforestation and forest rehabilitation must be done.International Journal of EnvironmentVolume-6, Issue-4, Sep-Nov 2017, page: 1-27